PanStop: a decade of rapid containment exercises for pandemic preparedness in the WHO Western Pacific Region - Edna Moturi; Katherine Horton; Leila Bell; Lucy Breakwell; Erica Dueger (World Health Organization Regional Office for the Western Pacific, 2019)
Rapid containment (RC) is one of the five priority interventions of the World Health Organization (WHO) Strategic Action Plan for Pandemic Influenza;1 it relies on the concept that mass prophylactic administration of antiviral drugs, combined with quarantine and social distancing measures, could contain or delay the international spread of an emerging influenza virus.2,3 During a RC operation, mass antiviral prophylaxis treatment and non-pharmaceutical interventions are rapidly implemented within a containment zone surrounding the initial cases; active surveillance and additional activities are extended to a broader buffer zone where cases are most likely to appear based on the movements of cases and contacts.2,4 The strategy is dependent on the rapid (within three to five days) detection, investigation and reporting of initial cases; the efficacy and availability of antivirals and vaccines; and timely risk assessment and decision-making. In the Western Pacific Region, a stockpile of antiviral medication and personal protective equipment acquired through donations from the Government of Japan is warehoused in Singapore under the auspices of the Association of Southeast Asian Nations (ASEAN),5 and is managed under contract by the Japan International Cooperation System (JICS).5 These supplies are reserved for early intervention when initial signs of increased human-to-human transmission of a highly contagious influenza virus occur.